UJI AKTIVITAS ANTIBAKTERI AIR PERASAN BUAH TIMUN (CUCUMIS SATIVUS) TERHADAP PERTUMBUHAN BAKTERI PROPIONIBACTERIUM ACNES SECARA IN VITRO - hafizah dina trisuci (Universitas Citra Bangsa, 2020)
Cucumber plant cucumis sativus can be used in medicine for their several medical benefits. It contain substances such as flavonoid, triterpene, saponin, and phosphorus which have antimicrobial properties. To prove this, antimicrobial activity test in vitro needs to be done with disc diffusion method at concentration of 25%, 50%, 75%, and 100% with two repetitions against propionibacterium acnes which are gram positive. Based on the results of the research that has been done, it can be concluded that the cucumber juice (cucumis sativus) used in the experiment and a weak effect on the growth of propionibacterium acnes bacterias of 100% concentration with a mean of inhibitory zone diameter of 11,3 mm. Keywords: Cucumber (cucumis sativus), propionibacterium acnes, antimicrobial